2001
DOI: 10.1046/j.1365-2923.2001.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Career obstacles for women in medicine: an overview

Abstract: Organizations in the field of medicine can look to the business world for 'best practices' aimed at advancing women to incorporate in their own organization. Medical schools and other institutions are taking the issue seriously as can be seen from the variety of government and institution-based initiatives directed at improving the role of women in medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 51 publications
2
92
1
10
Order By: Relevance
“…20 It has been suggested that this sex imbalance may be caused by rigidity in medical training programs and sex-based discrimination. 21 The 31-to 40-year modal age group in the present study is similar to that in previous reports in Nigeria 5 and America, 22 and reflects both disruption in the educational process and the current practice of most graduates working in the private or public health sector to attain financial stability before enrolling in a specialist training program. The spectrum of career choice was biased in favor of clinical specialties.…”
Section: Discussionsupporting
confidence: 88%
“…20 It has been suggested that this sex imbalance may be caused by rigidity in medical training programs and sex-based discrimination. 21 The 31-to 40-year modal age group in the present study is similar to that in previous reports in Nigeria 5 and America, 22 and reflects both disruption in the educational process and the current practice of most graduates working in the private or public health sector to attain financial stability before enrolling in a specialist training program. The spectrum of career choice was biased in favor of clinical specialties.…”
Section: Discussionsupporting
confidence: 88%
“…Reed & Buddeberg-Fischer (2001) argue that as it is in specialty choices that the significant gender differences are displayed, which indicates that obstacles for equal career goals are due to rigidity in career structures, and that gender discrimination acts synergistically with domestic responsibilities and parenting. Therefore, there is a risk of gender blindness if we uncritically rely on old ideals and the oath of a calling, when facing a new generation of parenting doctors.…”
Section: Gender Issues In Medical Socializationmentioning
confidence: 99%
“…La Encuesta de Población Activa (EPA) del INE también confirma esta tendencia a acortar distancias entre hombres y mujeres en puestos de dirección y responsabilidad. No obstante, esta tendencia positiva no es igual en los diferentes ámbitos: el crecimiento de la participación de la mujer en cargos directivos y de gestión en las instituciones sanitarias parece haber crecido poco, a pesar de la feminización de la profesión médica (Arrizabalaga y VallsLlobet, 2005;Reed et al, 2001, Reed, 2001.…”
Section: Algunas Explicaciones Teóricas Para Las Diferencias De Génerunclassified
“…Finalmente, una parte de la literatura apunta que las exigencias a las que están sometidas las mujeres hacen que éstas terminen por disminuir su rendimiento y, probablemente, su éxito en la trayectoria laboral. Todas estas variables interactúan obstaculizando la promoción jerárquica entre las médicas (Reed et al, 2001). No obstante, hay que analizar con cuidado aquella variable que está relacionada con las exigencias y con las dinámicas dentro de las instituciones sanitarias y, en particular, de los hospitales.…”
unclassified